L'efficacité du modèle d'apprentissage Example Non-Example pour la production écrite aux élèves de la classe XI MIPA de SMA Negeri 3 Pati - Nungki Astriani, Faradita; Al Adawiyah, Aisyiah (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
In French language learning, SMA Negeri 3 Pati students experience difficulties in writing skills, especially in Passé composé topics. The purpose of this research is to describe the implementation of Example Non-Example learning model and explain the effectiveness of Example Non-Example learning model. The sample selection in this study used a random sampling technique and obtained XI MIPA 3 class as the control group using the lecture method and XI MIPA 6 class as the experimental group using the Example Non-Example learning model. This research is included in quantitative research using an experimental design. Based on the t-test data analysis results, the t-count was 1.851 and Df = 58 at a significance level of 5%, so it is known that the t-table value is 1.67, indicating that the t-count is greater than the t-table. This shows that using the Example Non-Example learning model significantly influences learning to write French essays for class XI MIPA students at SMA Negeri 3 Pati.